Perception towards pineapple variety MD2 among pineapple farmers in Johor - Ismail Chong, Nurul Aesyah (2014)
This study was conducted to study the perception towards MD2 pineapple among pineapple farmers in Johor. Objective of this study is to examine the MD2 Pineapple acceptance among pineapple farmers in Johor. This study are using close-ended questionnaire to interview the respondents. The questionnaires distributed to 100 respondents among pineapple farmers in Johor. The data collected were analyzed using SPSS software and the analysis was based on descriptive analysis, chi-square analysis and logistic regression analysis. Findings from this survey showed that 24% of the respondents were planting MD2 pineapple. Main factor respondents planting MD2 pineapple are encouragement from MPIB, MD2 pineapple is higher quality and higher yielding than other pineapple variety. The main reason for respondents do not planting MD2 are MD2 pineapple suckers are too expensive and difficult to get it and no support from related agencies. Most respondents agreed that their current pineapple production is enough without planting MD2 pineapple. From chi-square analysis, demographic profiles do not influence respondents perception towards MD2 pineapple and do not influence respondents knowledge about pineapple farming. Even though the respondents have a different background, but all of them have a high level of knowledge, attitudes, practices and skills about pineapple farming. Furthermore, MPIB play an important role in giving extension programs to pineapple farmer to encourage them to grow pineapple especially MD2 pineapple. Based on the logistic regression, total income and total yield are significant at the 0.05 level. Total income indicates 0.185 times more intent to implement MD2 pineapple while yield indicate 0.087 times more intent to implement MD2 pineapple in their farm.